2020
DOI: 10.1101/2020.11.25.20238527
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of prediction models for short term outcome in COVID-19 patients in the emergency department: a retrospective study

Abstract: IntroductionCoronavirus disease 2019 (COVID-19) has a high burden on the healthcare system and demands information on the outcome early after admission to the emergency department (ED). Previously developed prediction models may assist in triaging patients when allocating healthcare resources. We aimed to assess the value of several prediction models when applied to COVID-19 patients in the ED.MethodsAll consecutive COVID-19 patients who visited the ED of a combined secondary/tertiary care center were included… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The AUC we observed was higher than in the original research, which is unusual for external validation, but this was also true in other validation studies done in the United Kingdom and the Netherlands 8,10 . The higher discriminability in our study may in part because we examined a more heterogeneous cohort that included patients who visited the emergency department but were not admitted to hospital.…”
Section: Discussionsupporting
confidence: 79%
“…The AUC we observed was higher than in the original research, which is unusual for external validation, but this was also true in other validation studies done in the United Kingdom and the Netherlands 8,10 . The higher discriminability in our study may in part because we examined a more heterogeneous cohort that included patients who visited the emergency department but were not admitted to hospital.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, only relatively healthy patients were transferred to the ICU for mechanical ventilation. A recent study in our center showed that, of all admitted COVID-19 patients, 35.2% had some form of treatment restrictions ( 46 ). This shows that COVID-19 related coagulopathy is not limited to patients with multiple comorbidities since our study sample with relatively healthy individuals presents with significant hemostatic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the variability of presenting pictures of COVID-19 and their progression, and the increasing burden the pandemic imposes on healthcare systems (9), the necessity arose for a tool of risk stratification, to allow early identification of COVID-19 patients at higher risk of mortality, using readily available objective criteria (8)(9)(10). A recent large size prospective cohort study (8) that seemed to outperform other risk stratification models (11).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the variability of presenting pictures of COVID-19 and their progression, and the increasing burden the pandemic imposes on healthcare systems (9), the necessity arose for a tool of risk stratification, to allow early identification of COVID-19 patients at higher risk of mortality, using readily available objective criteria (8)(9)(10). A recent large size prospective cohort study (8) utilized The International Severe Acute Respiratory and emerging Infections Consortium (ISARIC) World Health Organization (WHO) Clinical Characterisation Protocol to develop and validate such a tool (ISARIC 4C Mortality Score, hereafter referred to as ISARIC) that seemed to outperform other risk stratification models (11).…”
Section: Introductionmentioning
confidence: 99%